BASLER AFRIKA BIBLIOGRAPHIEN: Mitteilungen 7/8. Reprint 'Kriegsnachrichten: Tsumeb, Südwestafrika, 1915. - Bouch, R.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
The publishers of this Reprint deserve congratulation. With patience and no little effort they have brought together all fifteen issues of the virtually unknown Kriegsnachrichten published by Rudolf Kindt at Tsumeb between 15 May and 3 July 1915. At that time the German forces were isolated in the northern areas of the territory, and nearing the end of their resistance. Information on their activities has always been scarce and the availability of the Kriegsnachrichten will be a boon to researchers.